2021
DOI: 10.1155/2021/9984494
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Activation of Basic Oxygen Furnace Slag Modified Gold Mine Tailings for Building Material

Abstract: The mining industry generates large quantities of waste as tailings. The tailings have an adverse environmental impact. This study explored the utilization and stabilization of Barberton gold mine tailings (GMTs) and basic oxygen furnace slag (BOFS) to synthesize geopolymers for other applications. The geochemical, chemical, and geotechnical properties of GMT, BOFS, GMT geopolymer, and GMT: BOFS geopolymer were also studied. Sodium hydroxide (NaOH) and potassium hydroxide (KOH) were used as alkaline activators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Mine tailings are a waste material from the mining industry generated during the separation of valuable minerals from invaluable waste [45]. Recent investigations on one-part AAMs used gold mine tailings (GMT), iron ore mine tailings (IMT), lead-zinc mine tailings (LZMT), and vanadium tailings (VT) as precursors [46][47][48][49][50]. GMTsa waste material from mining goldmainly consist of SiO 2 and Al 2 O 3 , and their mineral phase structure is highly crystalline with peaks including quartz, albite, microcline, and muscovite [51].…”
Section: Mine Tailingsmentioning
confidence: 99%
“…Mine tailings are a waste material from the mining industry generated during the separation of valuable minerals from invaluable waste [45]. Recent investigations on one-part AAMs used gold mine tailings (GMT), iron ore mine tailings (IMT), lead-zinc mine tailings (LZMT), and vanadium tailings (VT) as precursors [46][47][48][49][50]. GMTsa waste material from mining goldmainly consist of SiO 2 and Al 2 O 3 , and their mineral phase structure is highly crystalline with peaks including quartz, albite, microcline, and muscovite [51].…”
Section: Mine Tailingsmentioning
confidence: 99%
“…Sithole et al [ 112 ] studied the mechanical performance of fly ash modified BOFS-based geopolymer masonry bricks and concluded that to meet the ASTM C34-13 for masonry bricks, the most favorable conditions for the geopolymer synthesis were 10% fly ash, 5M sodium hydroxide, and 80 °C curing temperature. In another study, Mashifana et al [ 111 ] explored the utilization of BOFS and gold mine tailings (GMT) for geopolymer synthesis and found that the 5 days compressive strength of the GMT: BOFS geopolymer cured at 90 °C was 20 MPa and 25.7 MPa for sodium hydroxide and potassium hydroxide alkaline activators, respectively, which satisfied the ASTM 34-17a and SANS 227:2007 for burnt masonry units, mine backfill paste, and lightweight civil works. Lee et al [ 113 ] reported the stabilization of BOFS geopolymer and found that the 28-day compressive strength was 30–40 MPa, and its expansion was less than 0.5% after the ASTM C151 autoclave testing.…”
Section: Resultsmentioning
confidence: 91%
“…Figure 10 shows that the morphology of BOFS is composed of non-spherical glassy irregularly shaped microstructures. The observed rougher and cloudy texture surface is attributed to the presence of CaO [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Geopolymer is an aluminosilicate material with a three-dimensional amorphous structure formed by alkali-excited active aluminosilicate minerals, and the reaction process is called alkali-excited geopolymerization. , Compared with the current common utilization methods, the comprehensive utilization of phosphate mine solid waste by the alkali-excited geopolymerization reaction is a new sustainable method that can treat phosphorus tailings, phosphogypsum, and yellow phosphorus slag in a low-cost and environment-friendly way, which can turn them into treasures and improve the comprehensive utilization rate of phosphate mine solid waste. Geopolymer is an environmentally friendly cementitious material with good mechanical properties, which can dissipate a large amount of solid waste and is used in different fields as a substitute for ordinary silicate cement. , Li et al investigated the effects of blending gypsum dihydrate, flue gas desulfurization gypsum, and phosphogypsum on the compatibility and mechanical properties of red mud slag slurry materials with different gypsum contents. Shi et al added modified quartz sand to the phosphogypsum cementitious filling slurry, which can effectively improve the phosphate contamination in the process of phosphogypsum cementation and filling.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Compared with the current common utilization methods, the comprehensive utilization of phosphate mine solid waste by the alkali-excited geopolymerization reaction is a new sustainable method that can treat phosphorus tailings, phosphogypsum, and yellow phosphorus slag in a low-cost and environment-friendly way, which can turn them into treasures and improve the comprehensive utilization rate of phosphate mine solid waste. 13 16 Geopolymer is an environmentally friendly cementitious material with good mechanical properties, which can dissipate a large amount of solid waste and is used in different fields as a substitute for ordinary silicate cement. 17 , 18 Li et al 19 investigated the effects of blending gypsum dihydrate, flue gas desulfurization gypsum, and phosphogypsum on the compatibility and mechanical properties of red mud slag slurry materials with different gypsum contents.…”
Section: Introductionmentioning
confidence: 99%